Civil Society Boundary Crossing and Elite Integration - Arvidson, Malin; Uhlin, Anders (Civil Society Elites, 2024)
This chapter explores elite boundary crossing between civil society and other societal sectors—including the state, party politics, and business—and how this may lead to inter-elite integration. We illustrate how qualitative life-work history interviews provide an important complement to established quantitative approaches to the study of elite integration. Through these interviews, we explore the drivers and motivations related to a boundary crossing career. The personal accounts of the boundary crossing experiences unveil essential aspects of the prerequisites of elite integration, if by integration we assume not only networking but also a degree of elite value congruence. This study identifies different motivations driving boundary crossing, making individuals more or less likely to contribute to value congruence. Those who move to another sector to impose values from their sector of origin typically contribute to value congruence. Those who leave a sector where they no longer feel at home and seek out new and more attractive values in another sector are less likely to contribute to value congruence. Those who move back and forth across sector boundaries to gain influence may or may not contribute to value congruence. This study opens up new ways of defining and exploring value congruence in elite integration studies. This chapter explores elite boundary crossing between civil society and other societal sectors—including the state, party politics, and business—and how this may lead to inter-elite integration. We illustrate how qualitative life-work history interviews provide an important complement to established quantitative approaches to the study of elite integration. Through these interviews, we explore the drivers and motivations related to a boundary crossing career. The personal accounts of the boundary crossing experiences unveil essential aspects of the prerequisites of elite integration, if by integration we assume not only networking but also a degree of elite value congruence. This study identifies different motivations driving boundary crossing, making individuals more or less likely to contribute to value congruence. Those who move to another sector to impose values from their sector of origin typically contribute to value congruence. Those who leave a sector where they no longer feel at home and seek out new and more attractive values in another sector are less likely to contribute to value congruence. Those who move back and forth across sector boundaries to gain influence may or may not contribute to value congruence. This study opens up new ways of defining and exploring value congruence in elite integration studies.